Black holes and gravitational solitons: stability, holography and beyond - Oliva - Zapata; Julio (2023)
PROJECT RESULTS: Describe the results of your research in reference to its original and/or modified Project objectives. The maximum extension of this section is 5 pages (Arial or Verdana font, size 10). Last year, I submitted the report for the first three stages of the project. Below, I will merge the results of this last stage with those reported last year. The results of this last stage of the project, include the publication of four new works along the lines of the proposal and the opening of new lines of research for the PI, co-Is and his students. In the final page, I declare the participation in conferences and seminars given in different institutions to disseminate the results of this project. Holography and gravity in lower dimensions: Results of the fourth year: Phys.Rev.D 103 (2021) 126010 and also the preprint “Hairy Black holes in General Minimal Massive Gravity” e-Print: 2106.12040 [hep-th] (submitted to EPJC) (1 publication and 1 preprint contributing to the original general goals 1,3) In the first paper, the geometrical interpretation of a conformally flat background that interpolates between AdS3 in the IR and a flat linear dilaton spacetime with Hagedorn spectrum in the UV, having passed through a transition region of positive curvature, is given. We studied the properties of this string background both from the point of view of the low-energy effective theory and of the worldsheet CFT. This paper was done in collaboration with Gaston Giribet and the student Ricardo Stuardo, who obtained his Master at Universidad de Concepción under the guide of Dr. Giribet and the PI. The second paper, is being evaluated at EPJC, and deals with the characterization of a hairy black hole geometry, when such spacetime is embedded as a solution of General Minimal Massive Gravity in 2+1, which is an example of a massive gravity theory in 2+1 that is devoid from the bulk/boundary clash. Since the physical properties of a geometry depend on the theory of which such geometry is a solution, we analyzed the algebra of ...